Critically Analysing the Hype of Sandbox in the Context of Fintech - Chenyu Xiao (Studies in Law and Justice, 2023)
The UK’s financial market is under severe pressure as its proportion in the international financial market is steadily decreasing. Intending to alter this phenomenon and “encourage the development of its FinTech ecosystem,”[i] so that the UK can keep pace with global financial developments, “closing the gap which has opened up between the UK and other global centres,”[ii] the Financial Conduct Authority (FCA) proposed the regulatory sandbox in 2015, which is “an environment in which FinTech businesses can test innovative products, services, business models and delivery mechanisms that stem from engaging in regulated activities.”[iii] Due to its ability to encourage FinTech innovations in companies while preventing consumer disruption, “since its launch in 2016,”[iv] it has rapidly gained popularity and taken the world by storm. However, some have contended that such a hype of the regulatory sandbox contributes to the failure in seriously assessing the benefits and the potential downsides of the instrument. As a result, the regulatory sandbox has now become a controversial topic. Based on these controversies, this essay analyze the regulatory sandbox and the Hype surrounding it and take the stance that the hype about sandbox may not take into account the conditions under which it has been successful and exaggerates the advantages of sandbox, which is not conducive to an objective evaluation.